2013
DOI: 10.1590/s0034-76122013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo sobre a implantação do orçamento baseado em desempenho na Autoridade Portuária de Valência

Abstract: O crescimento e o desenvolvimento da economia mundial têm dependido cada vez mais do transporte marítimo, e os portos são um elo importante nesse processo. O presente estudo tem como objetivo explorar a aplicação do orçamento baseado em desempenho no sistema de portos da Espanha. Para tanto, foi realizado um estudo sobre o modelo orçamentário do Sistema Portuário de Titularidade Estatal e um estudo de caso na Autoridade Portuária de Valência. Os resultados mostram que as mudanças no orçamento geraram maior int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
0
3
1
12
Order By: Relevance
“…The differences can be handled by extra-budgetary revenue and expenditure according to the need. This does not corroborate with the research by Lunkes et al (2013) in a Spanish port, which uses port traffic information, market analyses, economic indicators and national, regional and local strategic planning performance measures.…”
Section: Discussion Of the Resultscontrasting
confidence: 93%
See 3 more Smart Citations
“…The differences can be handled by extra-budgetary revenue and expenditure according to the need. This does not corroborate with the research by Lunkes et al (2013) in a Spanish port, which uses port traffic information, market analyses, economic indicators and national, regional and local strategic planning performance measures.…”
Section: Discussion Of the Resultscontrasting
confidence: 93%
“…To measure the performance, the main measures are the results from the previous years and the budgeted values, since the approved budget must be met, and the actual expenses must not exceed the performed revenue. Lunkes et al (2013) observed that in Spanish ports the main measures used are the values from previous years, benchmarking with other Spanish ports and from other countries, and the goals of the strategic plan. The purpose of the analysis of variances is to provide feedback for the budgeting of the following year, which corroborates with the fact that the execution uses mainly the values of the previous years.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Os resultados lançam luz sobre as práticas de gestão aplicadas no modelo de gestão pública de portos. Isso se torna importante uma vez que, além da própria Autoridade Portuária, toda a sociedade é alcançada pelos benefícios de uma boa gestão do porto, dado que ganhos em competitividade tende a refletir positivamente nos diversos setores econômicos na área de influência do porto (LUNKES et al, 2013;SOUSA et al, 2020).…”
Section: Considerações Finaisunclassified